2016
DOI: 10.5897/ajb2015.14958
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and nutrient utilization of Clarias gariepinus fed with different dietary levels of processed cassava leaves

Abstract: The growth performance of Clarias gariepinus fed with different dietary levels of processed cassava leaves and their nutrient utilized were studied for a period of 24 weeks. One hundred and forty four experimental Catfish (Clarias gariepinus) with 0.75±0.20 g mean weight and 3.9±0.31 cm mean total length were collected from Aqua-fish Consult, Awka, Anambra State, Nigeria. Eighteen rectangular plastic tanks were used for this study. Green cassava leaves (Manihot esculenta) were collected from a farm in Uda, Igb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Leaves of cassava as high protein from 22,6 to 30% (Syahrizal et al, 2017). Past study stated that the growth of Clarias gariepinus was optimum after fed 25% inclusion in the fish diet (Odo et al, 2016). In contrary, Aride et al (2016) found that diet for Tambaqui (Colossoma macropomum) consisting of 30% cassava reduced weight gain and specific growth rate.…”
mentioning
confidence: 98%
“…Leaves of cassava as high protein from 22,6 to 30% (Syahrizal et al, 2017). Past study stated that the growth of Clarias gariepinus was optimum after fed 25% inclusion in the fish diet (Odo et al, 2016). In contrary, Aride et al (2016) found that diet for Tambaqui (Colossoma macropomum) consisting of 30% cassava reduced weight gain and specific growth rate.…”
mentioning
confidence: 98%